Implementation of the Southern African development community protocol on education and training and its impact on economic development : A case study of Namibia and Zimbabwe - Namwandi, David R. (2014)
Since the Southern African Development Community Protocol on Education and Training (SADC-PET) was launched in 1997, only some of its member-states have implemented it into their national policy. This has resulted in the region’s failure, as a whole, to achieve the protocol’s objectives. As yet, no significant study or review has been carried out to investigate the exact causes for this. This study intends to examine two SADC member-states in order to determine precisely what steps have been taken to implement the protocol thus far. Using a mixed-method research design (qualitative and quantitative), the researcher presents a case-study of two of the 15 member-states and a data analysis of the remaining 13 member-states, to identify and explain the causes that have prevented the full implementation of the protocol. As well, a conceptual framework is presented, based on a review of the literature on education, economic development, economic growth, and educational management. The findings from this research reveal causes that have likely prevented the objectives of the protocol from being implemented and fully achieved by its member-states. Consequently, this study attempts to:  analyse the causes that have prevented the implementation of SADC-PET;  assess and evaluate the effectiveness of SADC-PET using Namibia and Zimbabwe as case studies;  identify and formulate appropriate recommendations to ensure the operationalisation of SADC-PET; and  sensitise and influence interested researchers to advance these findings through further research on the remaining 13 countries.